Digital well-being in an age of mobile connectivity: An introduction to the Special Issue. (May 2022) - Vanden Abeele, Mariek M. P.; Nguyen, Minh Hao
Although the ubiquitous connectivity afforded by mobile media brings benefits to people's work, social, and leisure lives, these benefits are sometimes overshadowed by the burdens of 24/7 connectivity, which challenge the well-being of individuals and society. Digital well-being is an emerging concept that refers to how people experience these benefits and burdens. This Special Issue brings together five articles that push the boundaries of digital well-being research by shedding light on the opportunities and challenges that people experience in relation to mobile connectivity, exploring the role of digital disconnection for digital well-being, and theorizing the conceptual underpinnings of digital well-being. In this editorial, we first give a definitional overview of the digital well-being concept and situate it in the field of mobile media and communication scholarship. Next, we identify two key issues that emerge from the Special Issue, and explain how the individual articles further our understanding of them. These issues are: (a) the strong conceptual link between digital well-being and digital disconnection; and (b) the conceptual difference between digital well-being as a psychological condition and as a socio-cultural artefact. To end, we present a future research agenda on digital well-being by first identifying current knowledge gaps, and next highlighting several themes that we anticipate as crucial in the forthcoming decade of digital well-being research in an age of mobile connectivity.